2009
DOI: 10.3949/ccjm.76a.08024
|View full text |Cite|
|
Sign up to set email alerts
|

Pregabalin for fibromyalgia: Some relief but no cure

Abstract: What is the role of pregabalin (Lyrica) in the treatment of fibromyalgia? In this article the authors explore the putative pathophysiology of fibromyalgia, pregabalin's mechanism of action and evidence of efficacy, and its emerging role in treating this challenging disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…A previous study demonstrated that pregabalin inhibited the release of NE and substance P via binding with the α-2-Δ subunit of voltage-gated presynaptic calcium channels to exert beneficial effects in FM symptoms (73). However, pregabalin produces only partial relief and does not cure FM (74). In the past few decades, medicines of herbal origin, including Rhizoma drynariae (75) and Baishao zongdai (68), demonstrated significant efficacy in terms of safety in the management of FM.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that pregabalin inhibited the release of NE and substance P via binding with the α-2-Δ subunit of voltage-gated presynaptic calcium channels to exert beneficial effects in FM symptoms (73). However, pregabalin produces only partial relief and does not cure FM (74). In the past few decades, medicines of herbal origin, including Rhizoma drynariae (75) and Baishao zongdai (68), demonstrated significant efficacy in terms of safety in the management of FM.…”
Section: Discussionmentioning
confidence: 99%
“…1), is a novel analogue of the neurotransmitter gamma amino butyric acid (GABA) with analgesic, anticonsulvant and anxiolytic activity. Pregabalin (Lyrica ® ) has been approved in 2007 by the US Food and Drug Administration (FDA) as the first drug for the treatment of fibromyalgia [1]. Pregabalin has been approved earlier by the FDA for the treatment of neuropathic pain and as an adjunctive therapy for refractory partial seizures [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34] The efficacy of these 2 compounds for the treatment of chronic pain has also been shown in clinical studies of diabetic and chemotherapy-induced neuropathic pain, postherpetic neuralgia, fibromyalgia and postoperative pain. 16,[18][19][20][21][22]31 In light of these observations, we hypothesize that alpha 2 -delta type voltage-dependent calcium channels mediate the effect of pregabalin on PDPH pain. Although pregabalin is chemically similar to c-aminobutyric acid (GABA), it is currently accepted that the activity of pregabalin does not include GABAergic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…14 Pregabalin, a ligand of the alpha 2 -delta type voltage-dependent calcium channels, reduces calcium influx at the nerve terminals and attenuates the release of glutamate, substance P and norepinephrine at the synapses. [15][16][17] Alpha 2 -delta type voltage-dependent calcium channels have recently become a treatment target for some chronic pain conditions. The efficacy of pregabalin as an analgesic agent has been shown in many clinical studies.…”
Section: Introductionmentioning
confidence: 99%